The Economic Potential of Lifting Trade Restrictions in Palestine - Eid, Ahmad Ihab Ahmed (2025)
This thesis examines the economic potential that could be achieved through the systematic removal of trade restrictions in Palestine. Using a mixed-methods approach that combines comparative case study analysis of South Africa, Vietnam, and Myanmar with quantitative economic modeling, the research assesses how lifting three primary categories of restrictions—the Gaza blockade, the limited access to land and resources in Area C of the West Bank, and the severely limited access to international markets—could transform the Palestinian economy. The findings suggest that trade liberalization could significantly stimulate economic growth, reduce unemployment, and increase export opportunities across multiple sectors of the Palestinian economy. The research identifies several promising growth sectors and proposes a comprehensive policy framework with short-term, medium-term, and long-term measures to facilitate economic development. While acknowledging that economic progress alone cannot resolve the complex political challenges in the region, this thesis contributes to understanding pathways toward sustainable development and improved livelihoods for Palestinians through a more open and integrated economy.